2017
DOI: 10.1007/s13373-017-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

Regularity of aperiodic minimal subshifts

Abstract: At the turn of this century Durand, and Lagarias and Pleasants established that key features of minimal subshifts (and their higher-dimensional analogues) to be studied are linearly repetitive, repulsive and power free. Since then, generalisations and extensions of these features, namely α-repetitive, α-repulsive and α-finite (α ≥ 1), have been introduced and studied. We establish the equivalence of α-repulsive and α-finite for general subshifts over finite alphabets. Further, we studied a family of aperiodic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In particular, it was shown in [38] that power free and repulsive are equivalent and, as we will shortly see, we have that power free and 1-finite (Definition 2.13) are equivalent. The general result follows, by combining these observations with Theorem 3.1 of [24] where it is shown that 1-repulsive and 1-finite are equivalent.…”
Section: 2mentioning
confidence: 71%
See 3 more Smart Citations
“…In particular, it was shown in [38] that power free and repulsive are equivalent and, as we will shortly see, we have that power free and 1-finite (Definition 2.13) are equivalent. The general result follows, by combining these observations with Theorem 3.1 of [24] where it is shown that 1-repulsive and 1-finite are equivalent.…”
Section: 2mentioning
confidence: 71%
“…The following proposition, which is proven in Section 5.1, relates the notions 1-repulsive and repulsive. In fact, in a sequel to this article [24], this result is shown to hold for general subshifts over finite alphabets. In particular, it was shown in [38] that power free and repulsive are equivalent and, as we will shortly see, we have that power free and 1-finite (Definition 2.13) are equivalent.…”
Section: Theorem 28 ([50]mentioning
confidence: 76%
See 2 more Smart Citations